Macroinvertebrate Assemblages and Water Quality in Batang Baleh, Kapit , Sarawak - Anita, Muli (Universiti Malaysia Sarawak (UNIMAS), 2017)
A study on macroinvertebrate assemblages and water quality of Batang Baleh was conducted between April 2014 and August 2015. This study aimed to determine the species diversity of macroinvertebrates, to assess the water quality of Batang Baleh tributaries, and to determine the functional feeding groups of macroinvertebrate according to stream orders. In total, 58 streams were studied and divided into four main areas namely, Entawau, Singut, Gaat and Mengiong. Stream temperatures were slightly warm (range: 21.00°C-29.19°C), alkaline (pH range: 6.08-7.90), with high DO (range: 6.0-8.2 mg/L). The water was clear during no rain, and turned muddy after the rains (turbidity range: 0.00-394.18 NTU). The water conductivity ranged from 15.00 to 87.10 mS/cm. The water quality based on National Water Quality Standard (NWQS) by DOE, were classified Batang Baleh streams between Class I and Class II. A total of 5,616 individual macro invertebrate were collected during this study, representing 13 Orders, 62 Families, and 112 Genera. Aquatic insects made up 94% of the total individuals, which Ephemeroptera found the most abundant (44%). Shannon index for four study areas ranged from 2.29-2.60, while evenness (0.52-0.92) and Margalefs (1.32 2.57). Both ACE and Jack 1 estimators estimate the macroinvertebrates observed species is ..... 119, and seven species not caught. However, Chao 1 estimates the species occurred is 129 species and 17 species not captured. The multivariate analysis for Principal Component analysis (PCA) and Non-metric Dimensional Scaling (NMDS) showed turbidity is associated with the distribution of macro invertebrate in the Mengiong streams. Gathering-collectors were revealed the most abundant in 58 streams of Batang Baleh.